Insights into embryonic chromosomal instability: mechanisms of DNA elimination during mammalian preimplantation development - Budrewicz, Jacqueline; Chavez, Shawn L. (Frontiers in Cell and Developmental Biology, 2024)
Mammalian preimplantation embryos often contend with aneuploidy that arose either by the inheritance of meiotic errors from the gametes, or from mitotic mis-segregation events that occurred following fertilization. Regardless of the origin, mis-segregated chromosomes become encapsulated in micronuclei (MN) that are spatially isolated from the main nucleus. Much of our knowledge of MN formation comes from dividing somatic cells during tumorigenesis, but the error-prone cleavage-stage of early embryogenesis is fundamentally different. One unique aspect is that cellular fragmentation (CF), whereby small subcellular bodies pinch off embryonic blastomeres, is frequently observed. CF has been detected in both in vitro and in vivo-derived embryos and likely represents a response to chromosome mis-segregation since it only appears after MN formation. There are multiple fates for MN, including sequestration into CFs, but the molecular mechanism(s) by which this occurs remains unclear. Due to nuclear envelope rupture, the chromosomal material contained within MN and CFs becomes susceptible to double stranded-DNA breaks. Despite this damage, embryos may still progress to the blastocyst stage and exclude chromosome-containing CFs, as well as non-dividing aneuploid blastomeres, from participating in further development. Whether these are attempts to rectify MN formation or eliminate embryos with poor implantation potential is unknown and this review will discuss the potential implications of DNA removal by CF/blastomere exclusion. We will also extrapolate what is known about the intracellular pathways mediating MN formation and rupture in somatic cells to preimplantation embryogenesis and how nuclear budding and DNA release into the cytoplasm may impact overall development.